Pemanfataan Serbuk Sekam Padi Sebagai Adsorben Untuk Menurunkan Konsentrasi Senyawa Piridaben Pada Pestisida Samite 135EC - Roni Saputra; Hengky Oktarizal (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2017)
Pesticides are very useful in many areas of human activities, especially in agriculture to ensure food availability. However, pesticides also have a negative impact on the environment and health. Pesticides are classified as endocrine disrupting chemicals (EDCs), which are chemicals that can interfere with the metabolic system, binding and eliminating hormones in the body, one of which is the danger of carcinogenicity. The concentration hazard present in Pesticide was experiment to decrease the concentration by using rice husk absorbent powder. This research is an experimental research that aims to reduce the concentration of pyridaben compounds contained in pesticides by using rice husk absorbent powder. By varying the sample treatment, variations of optimum concentrations of 10, 20, 30, 40 and 50 mg/L, contact time of 12 hours, 24 hours, 2 days, 4 days and 7 days, and weight of rice husk powder 25, 50, 100, 150, 200 mg. Analysis performed on pesticides is the content of pyridaben in pestisida samite 135EC. From this research, the best result was obtained at concentration 30 mg/L with 29,74% absorption efficiency, 24 hours contact time with 92,36% absorption efficiency, and 150 mg of rice husk powder with 54,88% absorption efficiency. This condition indicates that rice husk powders are effectively used to decrease the concentration of pyridaben compounds because of their effectiveness above 50%.